Meningkatkan Kepercayaan dan Kolaborasi Komunitas dalam Pendidikan Inklusif: Mengatasi Tantangan, Kebijakan, dan Kompetensi Guru - Henny Suharyati; Novita, Lina; Yelni Rahmawati (Jurnal Pendidikan dan Pengajaran, 2025)
Inclusive education plays an important role in providing equal learning opportunities for all children, regardless of their abilities. This research addresses the issue of low public trust in inclusive education, which has the potential to hinder policy implementation and practice. The aim of this research is to develop strategies to strengthen community trust and improve the quality of inclusive education. A mixed methods approach was used in this study. Data were collected through observation, semi-structured interviews with teachers, parents, students and policymakers and a survey of 255 respondents. The instrument used was an observation sheet. After the data was collected, it was analyzed through two stages, namely qualitative and quantitative. Qualitative analysis was conducted with thematic and narrative coding, while quantitative analysis used descriptive statistics and multivariate analysis. The results show that community involvement, teacher training and removing stigma are the main factors in increasing community trust in inclusive education. However, community trust does not have a significant effect on inclusive education outcomes directly. The study concluded that community-based strategies supported by teacher training and anti-stigma campaigns need to be implemented to improve community acceptance of inclusive education.